2020
DOI: 10.1101/2020.06.08.139477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Inexpensive RT-PCR Endpoint Diagnostic Assay for SARS-CoV-2 Using Nested PCR: Direct Assessment of Detection Efficiency of RT-qPCR Tests and Suitability for Surveillance

Abstract: With a view to extending testing capabilities for the ongoing SARS-CoV-2 pandemic we have developed a test that lowers cost and does not require real time quantitative reverse transcription polymerase chain reaction (RT-qPCR). We developed a reverse transcription nested PCR endpoint assay (RT-nPCR) and showed that RT-nPCR has comparable performance to the standard RT-qPCR test. In the course of comparing the results of both tests, we found that the standard RT-qPCR test can have low detection efficiency (less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Nearly similar IC 50 values were also noted in the growth inhibition of the B.6 variant (GISAID ID: EPI_ISL_458075; virus ID-hCoV-19/India/TG-CCMB-O2-P1/2020) of SARS-CoV-2 (earlier in May 2020) isolated at BSL-3 facility, CSIR-CCMB, Hyderabad (Supp Fig. 2) [14]. Inhibition of SARS-CoV-2 multiplication by 2-DG was also measured by estimating the nucleocapsid protein of the virus in Vero E6 cell lysate.…”
Section: -Dg Inhibits Sars-cov-2 Replicationsupporting
confidence: 53%
“…Nearly similar IC 50 values were also noted in the growth inhibition of the B.6 variant (GISAID ID: EPI_ISL_458075; virus ID-hCoV-19/India/TG-CCMB-O2-P1/2020) of SARS-CoV-2 (earlier in May 2020) isolated at BSL-3 facility, CSIR-CCMB, Hyderabad (Supp Fig. 2) [14]. Inhibition of SARS-CoV-2 multiplication by 2-DG was also measured by estimating the nucleocapsid protein of the virus in Vero E6 cell lysate.…”
Section: -Dg Inhibits Sars-cov-2 Replicationsupporting
confidence: 53%
“…Our results are in line with the results from Davda et al's study. They reported 13% false-negative among samples with negative real-time PCR results (17). Also, Wang et al reported 14 positive real-time PCR results among 156 samples (8.97%) with negative real-time PCR results (9).…”
Section: Resultsmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has caused a flurry of activity regarding the detection of SARS-CoV-2, in particular a substantial amount of new RT-PCR primers were developed for this specific purpose [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A number of factors can influence the reliability of the PCR detection, such as sample contamination [20], cross-reactivity with other viruses [14], contamination of reagents [21], non-specific annealing [22] and poor amplification efficiency [23].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we analyse how and if mismatches do influence the melting temperatures of primer/probes hybridised to SARS-CoV-2 genomes. We collected 19 PCR primer/probe sets (297 primers and 43 probes) which cover seven different gene regions of SARS-CoV-2 genome (N, E, S, M, ORF1ab, RdRp and nsp2 genes) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. These primer/probes were aligned to 21665 genomes of SARS-CoV-2 and 323 genomes of other coronaviruses.…”
Section: Introductionmentioning
confidence: 99%